Modified Hasson technique: a quick and safe entry of first port into the abdomen - George, Robinson; Radhakrishna, Veerabhadra; Mathew, Mebin; Thenamangalath, Aswini; Rahman, Ashna (International Surgery Journal, 2019)
Background: Laparoscopy is the standard technique for abdominal surgeries. There has been a debate over the safest laparoscopic entry technique over the past two decades. But, no technique has been regarded as the best, leading to numerable techniques. We use a modified Hasson technique to enter the peritoneal cavity. Hence, we conducted a study to evaluate the efficacy of our modified Hasson technique. Methods: A retrospective study was conducted in the Department of General Surgery, Al Azhar Medical College Hospital from January 2013 to December 2018. Results: A total of 156 patients were studied. Inguinal hernia repair was the most common indication. The mean entry time was 2±0.7 minutes. The postoperative complications included port site seroma [1 (0.6%)] and port site infection [1 (0.6%)]. Both the complications were found at the umbilical port and all following surgery for appendicular perforation. There was no incidence of preperitoneal placement of port, intraabdominal injury, port site hematoma or port site hernia. There was no mortality in the study group. Conclusions: Modified Hasson technique is a safe and quick technique to enter the abdomen.